An analysis of EU anti-dumping cases against China - Mai, Y.H. (2002)
In this study, an analysis of Chinese exports to the European Union (EU) of the products subject to anti-dumping duties shows that anti-dumping measures tend to significantly reduce bilateral trade flows. The rise in Chinese exports to EU would have been more than 3 per cent higher without the imposition of 21 anti-dumping duties in 1995-1998. A close investigation of EU anti-dumping cases against China also reveals that calculation of anti-dumping margins suffers from imperfect information and is therefore highly likely to lead to biased rulings. The high rate of termination due to withdrawal of complaints poses the question whether the scheme encourages industries to use it to fight against "fair" competitionas opposed to "unfair" competition. - Reproduced.
Keywords: European Union; Protectionism